2000
DOI: 10.1002/(sici)1521-186x(200002)21:2<84::aid-bem2>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential promoting effect of 60 Hz magnetic fields on N-ethyl-N-nitrosourea induced neurogenic tumors in female F344 rats

Abstract: The present study investigated the possible effect of 60 Hz magnetic fields (MFs) as promoters of neurogenic tumors initiated transplacentally by a chemical carcinogen, N-ethyl-N-nitrosourea (ENU). In a preliminary study, 5 mg of ENU was shown to induce 30 to 40% neurogenic tumors in F344 rats offspring after 420 days of observation. In the present study, 400 female rats were divided into eight different groups (50 animals/group) and exposed in utero (on day 18 of gestation) to a single intravenous dose of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…On the other hand, Ansari and Hei reported that concurrent EMF (0.1 mT at 60 Hz) treatment dose not increase either the cytotoxicity or the degree of induction of CD59 − mutants by graded doses of γ-rays or N-methyl-N'-nitro-N-nitrosoguanidine in A L cells (26). Mandeville et al reported that 0.002-2 mT at 60 Hz EMFs have no promoter effect on neurogenic tumors in F344 female rats exposed to ENU transplacentally (27). The intensity of EMF employed in that study is considered to be very low to promote the induction of tumors by ENU.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ansari and Hei reported that concurrent EMF (0.1 mT at 60 Hz) treatment dose not increase either the cytotoxicity or the degree of induction of CD59 − mutants by graded doses of γ-rays or N-methyl-N'-nitro-N-nitrosoguanidine in A L cells (26). Mandeville et al reported that 0.002-2 mT at 60 Hz EMFs have no promoter effect on neurogenic tumors in F344 female rats exposed to ENU transplacentally (27). The intensity of EMF employed in that study is considered to be very low to promote the induction of tumors by ENU.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in rodents evaluating brain tumour promotion have also been negative and have not given support for this idea. 24,25 The tendency toward an inverse association of occupational exposure may be the result of the crude exposure classification. The occupational exposure matrix was based only on job titles and branch of industry; no individual measurements were undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Mandeville et al, (2000) investigated the possible effect of 60 Hz magnetic fields as promoters of neurogenic tumors initiated transplacentally by ENU. Female Fischer rats were divided into eight different groups (50 animals/group) and exposed in utero (on day 18 of gestation) to a single intravenous dose of either saline (group I), or 5 mg/kg of ENU (groups II to VIII).…”
Section: Carcinogenicitymentioning
confidence: 99%